Optimization of cut-off grades and depletion rates by means of dynamic programming - Erhan Cetin; Abdurrahman Dalgic (Eximia, 2024)
The determination of cut-off grades is critical for mine appraisal. Because of the time value of money, an optimum schedule of cut-off grades must be used instead of determination of a single cut-off grade for the life of a mine. In order to achieve the maximum net present value, a decreasing order of cut-off grades schedule must be used because of the opportunity cost. In the optimization of cut-off grades by dynamic programming, the depletion rates to be searched are actually limiting the search area. The optimum can be found from among the alternative depletion rates. Selling prices of mining products are volatile and future values cannot be known. This paper describes the use of dynamic programming in cut-off grades optimization and further extension of the method to price volatility in selling prices of mining products. The author introduces the general background of use of dynamic programming in cut-off grades optimization and the case in uncertain market conditions. Software developed in this subject handles to find the optimum sequence of cut-off grades and depletion rates for mineral deposits under market uncertainty. Dynamic programming method can be used as a means of cut-off grades optimization in this context very robustly.